Paraneoplastic cerebellar degeneration in a patient with ovarian cancer - Hung-Ju Chien; Chuo-Yu Lee; Lu-An Chen; Chao-Chih Wu; Chih-Long Chang (Elsevier, 2015)
Objective: Herein, we report a case of ovarian serous carcinoma with paraneoplastic cerebellar degeneration. Case report: A 44-year-old female presented to our hospital with dizziness, slurred speech, and ataxic gait. Brain magnetic resonance imaging was normal. A lumbar puncture revealed a normal cell count in the cerebrospinal fluid, but slightly elevated protein. Her serum cancer antigen -125 level was high (2126.4 U/mL), and abdominal computed tomography disclosed a pelvic mass measuring 11 cm in diameter. Exploratory laparotomy was then performed, and a frozen section of the tumor revealed serous carcinoma. Conclusion: According to the surgical findings and pathological report, The International Federation of Gynecology and Obstetrics (FIGO) Stage IIIC, Grade 3, serous-type ovarian cancer was diagnosed. Due to the abovementioned symptoms and signs, we performed a serial test to document the presence of anti-Yo antibody in this patient.